Event Profile of Ankle Sprain Injury at Athletes in East Java Puslatda - Santoso, Pradana Mahendra; Tinduh, Damayanti; Chilmi, Mohammad Zaim (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background: Ankle injuries are the most common injuries in sports and often cause chronic pain, swelling, and functional instability. Ankle injuries (sprains) are acute injuries that athletes often experience. This acute injury is caused by a pressure force, for example, when making a sudden turning motion. Sprains can affect the ankle's side and damage the outside (lateral) ligament; ankle injuries were reported at the Sports Clinic RSUD Dr. Soetomo Surabaya . Aims: To understand the profile of ankle injuries suffered by East Java Puslatda athletes and investigate the risk factors for these injuries. Material and methods: The study was conducted using a retrospective approach with an analytic observational design in the form of a cross-sectional study because the researchers did not provide intervention to the research subjects and only made observations and secondary data profiling. Result: The data collection and analysis found that ankle injuries in East Java Puslatda athletes most often occur in the late adolescent age range (17-23 years), which is as high as 35.8%. Conclusions: There is no relationship between extrinsic and intrinsic factors on the risk of ankle injury for Puslatda East Java athletes.